Harmonizing Law Enforcement Officials Against Child Victims of Narcotics Abuse - Sibarani, Fauzi Anshari; Asmadi, Erwin (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Law No. 35/2009 on Narcotics explains that drug abuse is considered a crime without victims. In handling children who are involved in drug cases, the main principle that must be considered is the best interest of the child. This principle is contained in the Juvenile Justice System Law, which emphasizes that every decision must consider the welfare of the child's life and development. The legal protection of children caught up in drug abuse causes the boundaries between perpetrators and victims to become blurred, because according to the law, drug abuse is considered a criminal offense. Therefore, the legal establishment of both the Police, the Prosecutor's Office and the Judiciary needs harmonization so that the application to children who abuse drugs can be put forward, so that children can be given legal certainty in terms of justice. This study is to analyze the harmony of legal confirmation on children as victims of drug abuse. The method used is normative juridical research with a focus on literature study which uses secondary data. The conclusion of the research is that children as victims of narcotics abusers must be given sanctions in the form of rehabilitation, not imposed criminal sanctions because what children do is a crime but without causing victims (crime without victim), harmonization of law enforcement agencies (APH) in cases of children becoming victims of drug abusers must be aligned for the welfare of children.